Pengaruh Inhibitor Ekstrak Daun Jambu Biji (Psidium guajava) Terhadap Laju Korosi Selongsong Amunisi Kaliber 7.62 mm Dalam Media CH3COOH dan HCl - Andini Dyah Anugrahita; Ardian Infantono; Muhammad Sakti La Ore (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
Corrosion can occur in any metal, including brass metal as raw material for making ammunition casing. One way to inhibit corrosion is to use corrosion inhibitors which can be made using organic materials. Guava leaf (Psidium guajava) contain tannin compounds as corrosion inhibitors. In this study, the brass used was the casing of the MU-2TJ ammunition caliber 7.62 mm produced by PT. Pindad in 1992 and 1994. Corrosion rate was calculated by the method weight loss. Inhibitor preparation of guava leaf extract was carried out by maceration method, where 10 grams of dried guava leaf were dissolved in 100 mL water-ethanol solvent with various volume ratios of water : ethanol 7:3, 6:4, and 5:5, respectively. Brass with inhibitor and without inhibitor was immersed for 15 days or 360 hours in HCl and CH3COOH solution media. . The results showed that in CH3COOH media, the largest inhibitor efficiency was 42.12% by using guava leaf extract inhibitor with a ratio of volume water : ethanol 6:4 in CH3COOH 0.1 M solution, where the corrosion rate of brass without inhibitors is 4.34x10-6 mpy and the corrosion rate of brass with inhibitors is 2.51x10-6 mpy. In HCl media, the largest inhibitor efficiency was 7.52% by using guava leaf extract inhibitor with a ratio of volume water : ethanol 5:5 in HCl 0.05 M solution, where the corrosion rate of brass without inhibitors is 4.81x10-6 mpy and the corrosion rate of brass with inhibitors is 4,45x10-6 mpy.